The Influence of Workplace Incivility, Perceived Supervisor Support, and Job Satisfaction in Mediating Organizational Identification Has an Influence on Employee Performance in Teachers at the Yos Sudarso Karawang School - Chiquita Christella Chandra; Hetty Karunia Tunjungsari (Eduvest - Journal of Universal Studies, 2024)
This research describes the results of the analysis which concludes that workplace incivility has a negative influence on organizational identification, while perceived supervisor support and job satisfaction show a positive influence, although not always significant. Apart from that, it was found that organizational identification has a positive and significant influence on employee performance. These findings support previous research which reports that the relationship between these variables is complex and can influence employee performance. Therefore, this research not only provides a better understanding of the factors that influence teacher performance at the Yos Sudarso Karawang school, but also highlights the importance of paying attention to organizational identification in an effort to improve individual performance in an organizational context. In addition, through clear identification of the problem, scope, problem formulation, objectives and benefits of research, this research also contributes to further understanding of important issues in education in Indonesia.